Seeding Performances of No-Till Seeders Equipped with Different Furrow Openers, Covering Components and Forward Speeds for Winter Wheat - Ahmet Çelik; Sefa Altıkat (Journal of Agricultural Sciences)
In the no-till method, seeds are placed in rows opened by furrow openers that can work under stubble field conditions, and are covered with soil and plant residue using covering components. Furrow openers and their properties are extremely effective in sowing seeds at certain depths and intra-row distances for various emergence and growth conditions. The purpose of this study is to determine effects of no-till seeders with different furrow opener types, covering components and forward speeds on certain important physical properties of the soil, stubble distribution, and seed emergence of winter wheat. Two different types of no-till seeders; disc (NS-1) and narrow hoe (NS-2), two different types of covering components; chain (CC) and spring type (SC), and two forward speeds; FS-1 (0.75 m s-1) and FS-2 (1.5 m s-1) were used to achieve the purpose of this study. The no-till seeder with a disc type furrow opener achieved better stubble distribution on the soil surface and percentage of seed emergence in comparison to no-till seeder with narrow hoe type openers. The best coverage rate of stubble on the soil surface and percentage of seed emergence were obtained at the forward speed of 0.75 m s-1. While the spring type covering component increased percentage of seed emergence in comparison to thechain type covering component, it decreased the mean emergence time.